A Study of Students’ Efforts to Improve the Ability in English - Arin Arianti (Faculty of Language and Literature, University of Surakarta, 2021)
Non-English students need specific efforts to improve their English ability. Each student has a different effort in learning English. The research aims to find out the kinds of students’ efforts in improving their English ability and the dominant English skill practiced by the students. Besides, the level of students’ effort is also investigated in this research. The subjects of this research cover 35 students in the first semester of the Faculty Of Public Health. Qualitative method was used in this research by semi structured interviews as the primary tools of data collection. The result shows that students’ efforts to improve their English skills are varies. Students try to improve their ability in English aimed to the purpose of speaking or communication. The level students' efforts are categorized into the substantive effort.